FUTURE PROSPECTS FOR SOLVING THE PROBLEM OF HUNGER - Khayrilloev Sunnatillo (Лучшие интеллектуальные исследования, 2024)
Abstract: In a world where millions of people go hungry every day, finding sustainable solutions to tackle the problem of starvation is crucial. While progress has been made in reducing global hunger rates in recent years, challenges still remain. However, with advancements in technology and a growing awareness of the issue, there is hope for a brighter future. One promising avenue for addressing starvation is through the use of innovative agricultural practices. With climate change posing a threat to food security, there is a need for sustainable farming methods that can withstand extreme weather conditions and produce high yields. This includes techniques such as precision agriculture, vertical farming, and hydroponics, which can maximize crop production while minimizing resource use. By harnessing innovative agricultural practices, improving access to nutritious food, promoting education and leveraging technology, we can work towards a world where no one goes hungry. It will require collaboration between governments, organizations, and individuals at all levels to make this vision a reality. In this article, I try to explain how we can build a more sustainable and equitable future for all.